Analysis of student’s mathematical problem solving ability based on responsibility learning with themed problem based learning model - Dary, Novia Wulan; Wijayanti, Kristina; Winarti, Endang Retno (Department of Mathematics, Universitas Negeri Semarang, 2021)
The purposes of this research are to examine the differences in problem-solving abilities of seventh-grade students in quadrilateral material with the Themed Problem Based Learning and Problem Based Learning model and to examine the effect of students' responsibility towards the students' problem-solving abilities in quadrilateral material with Themed Problem Based Learning. This research uses a quantitative method. The population is the seventh-grade students in one of Junior High School in Bekasi in amount of 198 students. The selected samples are students grade VII-9 as an experimental group and students grade VII-8 as a control group. The methods of collecting data in this study are the method of test and questionnaire. Data analysis uses t-test and regression analysis test. The results of this research show that the average problem-solving abilities of students on Themed Problem Based Learning is over than the model of Problem Based Learning and the responsibility of the students' learning give an impact to the problem-solving abilities of students on Themed Problem Based Learning model.